30 years of rubberized concrete investigations (1990-2020). A bibliometric analysis - Zarhri, Zakaryaa; Rosado Martinez, William; Dominguez Lepe, Jose Antonio; Vega Azamar, Ricardo Enrique; Chan Juarez, Maritza; Pamplona Solis, Blandy Berenice (Revista ALCONPAT, 2022)
This work presents a bibliometric study of the literature on the use of recycled rubber from tires in the construction industry to promote its use as a ‘raw’ material to reduce pollution at a global level. Published papers between 1990 and 2020 in both databases Scopus and Web of Science (WoS) were taken into account using the Methodi Ordinatio and the VOSviewer software. A total of 967 documents on the use of recycled rubber in structural and non-structural concrete have been published during this time frame and 1182 authors have contributed on the subject. Since 2010, the interest of researchers to introduce recycled rubber in construction applications has increased markedly. China, the United States of America and Australia are the leading countries in rubberized concrete research.